Parameter Identification of a PMSG Using a PSO Algorithm Based on Experimental Tests - A. J. Mahdi; W. H. Tang; Q. H. Wu (Iraqi Journal for Electrical and Electronic Engineering, 2010)
An accurate model for a permanent magnet synchronous generator (PMSG) is important for the design of a high-performance PMSG control system. The performance of such control systems is influenced by PMSG parameter variations under real operation conditions. In this paper, the electrical parameters of a PMSG (the phase resistance, the phase inductance and the rotor permanent magnet (PM) flux linkage) are identified by a particle swarm optimisation (PSO) algorithm based on experimental tests. The advantages of adopting the PSO algorithm in this research include easy implementation, a high computational efficiency and stable convergence characteristics. For PMSG parameter identification, the normalised root mean square error (NRMSE) between the measured and simulated data is calculated and minimised using PSO.